The Icelandic translation of the Bath Adolescent Pain Questionnaires (BAPQ and BAPQ-P): Preliminary psychometric properties of multidimensional measures for adolescents with chronic pain and their parents to assess the impact of chronic pain on the adolescents - Silja Björg Halldórsdóttir 1987- (2016)
Chronic pain is common in adolescents and can have adverse effect on diverse areas of their lives including social, emotional, and cognitive functioning. The Bath Adolescent Pain Questionnaire (BAPQ) and the parent version (BAPQ-P) was developed to capture these multidimensional effects by including assessments of social functioning, family functioning physical functioning, general anxiety, development, pain specific anxiety, and depression. The aim of this study was to translate, into Icelandic, the BAPQ and BAPQ-P and examine their psychometric properties. Participants were 45 adolescents and 69 parents who had been experiencing chronic pain for the previous three months. The adolescents answered online: BAPQ, The Pediatric Quality of Life Inventory pediatric self-report (PedsQL self-report), The Children’s Depression Inventory (CDI), The Multidimensional Anxiety Scale for Children (MASC), and The Pain Catastrophizing Scale for Children (PCS-C). The parents answered online: BAPQ-P, The Pediatric Quality of Life Inventory parent proxy-report (PedsQL parent proxy-report), The Strength and Difficulties Questionnaire - Parental version (SDQ-P), The Pain Catastrophizing Scale for Parents (PCS-P), and The Pediatric Quality of Life Inventory Family Impact Module (PedsQL-FIM). Hringiðan Háskólinn í Reykjavík